A Comparative Study on Children’s Inheritance in Le Vietnam and Joseon Korea from the Fifteenth to the Seventeenth Centuries - Insun Yu (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Parents’ property was supposed to be divided equally among their children, regardless of their gender, in the early years of Le Vietnam and Joseon Korea. This tradition of the equal division could be influenced by Neo-Confucianism, which was an official ideology in both dynasties. However, this tradition had not changed not only in the Le dynasty, but also in the Nguyen dynasty. One of the main reasons behind no change in Le Vietnam was a period of political turmoil: conflicts between the Mạc/the Le, and between the Trinh/the Nguyen continued for 300 years, from the early 16th century to the end of the 18th century. Subsequently, Neo-Confucianism had dwindled. Conversely, the influence of Neo-Confucianism had been intensified in Joseon Korea over time. Ancestor ritual had become crucial and the direct lineal descendant had been considered to take precedence over others since the mid-17th century. He inherited a higher portion of parents’ property than his younger brothers and sisters. In short, there is an interesting contrast which displayed the influence of Neo-Confucianism in the two difference countries since the late 17th century: Le Vietnam and Joseon Korea. Received 6th July 2022; Revised 2nd September 2022; Accepted 30th September 2022